Dietary weight loss and exercise interventions effects on quality of life in overweight/obese postmenopausal women: a randomized controlled trial - Wang Ching-Yun; Duggan Catherine; Xiao Liren; Bain Carolyn E; Foster-Schubert Karen E; Kong Angela; Alfano Catherine M; Imayama Ikuyo; Campbell Kristin L; Blackburn George L; McTiernan Anne (BMC, 2011)
Abstract Background Although lifestyle interventions targeting multiple lifestyle behaviors are more effective in preventing unhealthy weight gain and chronic diseases than intervening on a single behavior, few studies have compared individual and combined effects of diet and/or exercise interventions on health-related quality of life (HRQOL). In addition, the mechanisms of how these lifestyle interventions affect HRQOL are unknown. The primary aim of this study was to examine the individual and combined effects of dietary weight loss and/or exercise interventions on HRQOL and psychosocial factors (depression, anxiety, stress, social support). The secondary aim was to investigate predictors of changes in HRQOL. Methods This study was a randomized controlled trial. Overweight/obese postmenopausal women were randomly assigned to 12 months of dietary weight loss (n = 118), moderate-to-vigorous aerobic exercise (225 minutes/week, n = 117), combined diet and exercise (n = 117), or control (n = 87). Demographic, health and anthropometric information, aerobic fitness, HRQOL (SF-36), stress (Perceived Stress Scale), depression [Brief Symptom Inventory (BSI)-18], anxiety (BSI-18) and social support (Medical Outcome Study Social Support Survey) were assessed at baseline and 12 months. The 12-month changes in HRQOL and psychosocial factors were compared using analysis of covariance, adjusting for baseline scores. Multiple regression was used to assess predictors of changes in HRQOL. Results Twelve-month changes in HRQOL and psychosocial factors differed by intervention group. The combined diet + exercise group improved 4 aspects of HRQOL (physical functioning, role-physical, vitality, and mental health), and stress (p ≤ 0.01 vs. controls). The diet group increased vitality score (p < 0.01 vs. control), while HRQOL did not change differently in the exercise group compared with controls. However, regardless of intervention group, weight loss predicted increased physical functioning, role-physical, vitality, and mental health, while increased aerobic fitness predicted improved physical functioning. Positive changes in depression, stress, and social support were independently associated with increased HRQOL, after adjusting for changes in weight and aerobic fitness. Conclusions A combined diet and exercise intervention has positive effects on HRQOL and psychological health, which may be greater than that from exercise or diet alone. Improvements in weight, aerobic fitness and psychosocial factors may mediate intervention effects on HRQOL.